Non-Standard Employment Patterns in the Netherlands - Anne C. Gielen; Trudie Schils (Institute for the Study of Labor (IZA), 2014)
The Dutch labour market is the European leader in part-time employment. Both for men and women the incidence of part-time work is higher than in most other European countries. However, this does not imply that traditional employment i.e. full-time jobs have disappeared in the Netherlands. In fact, looking at aggregate figures masks the enormous heterogeneity in the incidence of atypical work across different occupations. This paper investigates trends in atypical work in the Netherlands in the period 1994-2008, where specific attention has been paid to differential trends across different occupations over time. We find that there is a huge amount of variety in atypical work across Dutch occupations. To a certain extent this matches the preferences of employees and employers in the Dutch labour market. However, some workers in particular low-skilled workers suffer from job insecurity and a lack of career prospects due to their limited possibilities to move to better jobs. The current economic crisis and the rising unemployment rate make their situation even more uncertain.
Keywords: J62; 330; atypical employment; labor market flexibility